(untitled) (Acta Scientiarum. Education, 2017)
On the 6th of December 2008, a police officer shot dead a teenager in Exarcheia, a central area in Athens. Within hours, the reactions turned into riots spreading across Athens. The Athens 2008 riots marked the beginning of the end of the years of affluence in Greece, which culminated symbolically with the 2004 Olympic Games. This paper proposes to read the December 2008 events back and ask to what extent these riots – symbolised by a graffiti on a wall in Athens saying ‘we are an image from the future’ - were a harbinger of the Greek crisis and of the generalised civil unrest which ensued and peaked between 2010-2012. With police data claiming that over 26,000 demonstrations have taken place across Greece since the December 2008 riots, civil unrest seems to have become endemic in the country, symptomatic of a crisis that is not only economic and social, but also political in the sense of the crisis of legitimacy of the State, its representatives and its institutions.